Potency of Yeasts Isolated from Shallot Rhizosphere to Control Basal Rot (Fusarium oxysporum f.sp. cepae) Disease on Shallot - Sri Hartati; Risma Yuniah Nur’haqi; Wahyu Daradjat Natawigena; Tarkus Suganda (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
One of the major diseases of shallots is basal rot disease caused by Fusarium oxysporum f.sp. cepae (FOC). Biocontrol agents can be used as an environmentally friendly control method. Some yeasts isolated from the rhizosphere may have the potencies to control soilborne plant pathogen such as FOC. This study was objected to obtain yeast isolates from the rhizosphere of shallots that have the potencies to control basal rot. The first step was isolation of yeasts from the rhizosphere of shallots and isolation of FOC. The yeast isolates were then tested for their potencies in suppressing FOC in vitro and decreasing the basal rot disease on the shallot plants. There were ten yeast isolates obtained from the rhizosphere of shallot, in which seven isolates were non pathogenic to shallot plant. These seven isolates were further tested for their potencies in controlling FOC and basal rot disease. The results showed that those isolates were able to inhibit the colony growth of FOC by 16,11% - 38,33% in the in vitro dual culture test, and 21,11% - 38,89% in the production of volatile compound test. The isolates also suppressed the basal rot disease incidences by 8,30% - 24,98%. Isolates Cm2 and Cm3 caused the highest disease suppression (24,98%).